Selection of Retroviral Reverse Transcription Primer Is Coordinated with tRNA Biogenesis - Kelly, Nathan J. (American Society for Microbiology, 2003)
Initiation of retrovirus reverse transcription requires the selection of a tRNA primer from the intracellular milieu. To investigate the features of primer selection, a human immunodeficiency virus type 1 (HIV-1) and a murine leukemia virus (MuLV) were created that require yeast tRNA(Phe) to be supplied in trans for infectivity. Wild-type yeast tRNA(Phe) expressed in mammalian cells was transported to the cytoplasm and aminoacylated. In contrast, tRNA(Phe) without the D loop (tRNA(Phe)D(−)) was retained within the nucleus and did not complement infectivity of either HIV-1 or MuLV; however, infectivity was restored when tRNA(Phe)D(−) was directly transfected into the cytoplasm of cells. A tRNA(Phe) mutant (tRNA(Phe)UUA) that did not have the capacity to be aminoacylated was transported to the cytoplasm and did complement infectivity of both HIV-1 and MuLV, albeit at a level less than that with wild-type tRNA(Phe). Collectively, our results demonstrate that the tRNA primer captured by HIV-1 and MuLV occurs after nuclear export of tRNA and supports a model in which primer selection for retroviruses is coordinated with tRNA biogenesis at the intracellular site of protein synthesis.